Parathyroid carcinoma survival: improvements in the era of intact parathyroid hormone monitoring? - Steve R. Martinez; Miya E. Allen; Anthony D. Yang; Alison Semrad (Rare Tumors, 2013)
The intact parathyroid hormone (iPTH) assay is a critical test in the diagnosis and management of PTH-mediated hypercalcemia, including parathyroid carcinoma (PCa). We hypothesized that the survival of patients diagnosed with PCa has improved since adoption of the iPTH assay into clinical practice. We identified all confirmed cases of PCa within the Surveillance, Epidemiology and End Results database from 1973 to 2006. Patients were categorized into two eras based upon introduction of the iPTH assay: 1973 to 1997 (era I) and 1997 to 2006 (era II, when the iPTH assay was in standard use). We estimated overall survival (OS) and disease-specific survival (DSS) using the Kaplan-Meier method, with differences among survival curves assessed via log rank. Multivariate Cox proportional hazards models compared the survival rates between treatment eras while controlling for patient age, sex, race/ethnicity, tumor size, nodal status, extent of disease, and type of surgery. Multivariate models included patients undergoing potentially curative surgery and excluded those with dis- tant metastases. Risks of overall and disease-specific mortality were reported as hazard ratios with 95% confidence intervals. Study criteria were met by 370 patients. Median survival was 15.6 years. Five-year rates of OS and DSS were 78% and 88% for era I and 82% and 96% for era II. On multivariate analysis, age, black race, and unknown extent of disease predicted an increased risk of death from any cause. Treatment era did not predict OS. No factor predicted PCa-specific mortality. In multivariate analysis, neither OS nor DSS have improved in the current era that utilizes iPTH for the detection and management of PCa.